2006
DOI: 10.1038/sj.ki.5000249
|View full text |Cite
|
Sign up to set email alerts
|

Redefinition of uremic cardiomyopathy by contrast-enhanced cardiac magnetic resonance imaging

Abstract: Patients with end stage renal failure (ESRF) have an increased risk of premature cardiovascular disease. Left ventricular (LV) abnormalities, so called 'uremic cardiomyopathy', are associated with poorer outcome. Cardiac magnetic resonance imaging (CMR) accurately defines LV dimensions and identifies underlying myocardial pathology. We studied the relationship between LV function and myocardial pathology in ESRF patients with CMR. A total of 134 patients with ESRF underwent CMR. LV function was assessed with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
188
4
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(203 citation statements)
references
References 39 publications
9
188
4
2
Order By: Relevance
“…Since 2002 (10,11,13), we have used CMR as part of the standard assessment of patients for renal transplantation. The renal transplant unit at the Western Infirmary (Glasgow, Scotland, UK) provides transplant services to a population of 2.8 million people in the west of Scotland.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2002 (10,11,13), we have used CMR as part of the standard assessment of patients for renal transplantation. The renal transplant unit at the Western Infirmary (Glasgow, Scotland, UK) provides transplant services to a population of 2.8 million people in the west of Scotland.…”
Section: Patientsmentioning
confidence: 99%
“…This technique has been established as the most accurate noninvasive method of assessing ventricular dimensions in patients, including those with stage 5 chronic kidney disease (10,11). In particular, measurements obtained by echocardiography tend to overestimate LVMI, particularly at higher values, when compared with CMR (12).…”
mentioning
confidence: 99%
“…It is characterized by a composite of inappropriate ventricular hypertrophy, marked interstitial fibrosis, microvessel disease with thickening of intramyocardial arteries, and capillary deficit (11). In a small biopsy controlled study, it was shown that cardiac fibrosis was a predictor of death (12). Cardiac fibrosis (causing arrhythmia as a result of reentry circuits) as well as diastolic malfunction (the result of reduced compliance [11]) are the most important causes of cardiac death and potentially future therapeutic targets.…”
Section: Underlying Cardiac Diseasementioning
confidence: 99%
“…In addition, among participants with more advanced kidney disease on dialysis, magnetic resonance imaging (MRI) with contrast demonstrates a diffuse pattern image with gadolinium uptake suggestive of fibrosis and non-ischemic cardiomyopathy [5]. Nowadays, the ratio of early diastolic mitral inflow velocity to early diastolic mitral annulus velocity (E/e′ ratio) is used for the evaluation of left ventricular filling pressure, and it has been used as a marker to diagnose diastolic heart failure (HF) [6,7].…”
Section: Introductionmentioning
confidence: 99%